Sustainable production of value-added N-heterocycles from biomass-derived carbohydrates via spontaneous self-engineering - Yu Feng; Liu Chong; Tan Fenghua; Liao Yuhe; Wang Liang; Li Yuping; Xiao Feng-Shou (National Science Open)
Abstract: Synthetic N-heterocyclic compounds, such as quinoxalines, have shown a crucial role in pharmaceutical as well as food and dye industries. However, the traditional synthesis toward N-heterocycles relies on multistep energy and cost-intensive non-sustainable processes. Here, we report a facile approach that allows one-step conversion of biomass-derived carbohydrates to valuable quinoxalines in the presence of aryl-1,2-diamines in water without any harmful metal catalysts/organic solvents via spontaneously engineering involved cascade reactions under hydrothermal conditions. Aryl-1,2-diamines are revealed as the key to propel this transformation through boosting carbohydrate fragmentation into small 1,2-dicarbonyl intermediates and subsequently trapping them for constituting stable quinoxaline scaffolds therefore avoiding a myriad of undesired side reactions. The tunability of product selectivity can be also achievable by adjusting the basicity of the reaction environment. Both batch and continuous-flow integrated processes were verified for production of quinoxalines in an exceptionally eco-benign manner (E-factor <1), showing superior sustainability and economic viability.